A mobile, web‐based system can improve positive airway pressure adherence. (8th December 2016) - Hostler, Jordanna M.; Sheikh, Karen L.; Andrada, Teotimo F.; Khramtsov, Andrei; Holley, Paul R.; Holley, Aaron B.
Summary: SleepMapper is a mobile, web‐based system that allows patients to self‐monitor their positive airway pressure therapy, and provides feedback and education in real time. In addition to the usual, comprehensive support provided at our clinic, we gave the SleepMapper to 30 patients initiating positive airway pressure. They were compared with patients initiating positive airway pressure at our clinic without SleepMapper (controls) to determine whether SleepMapper affected adherence. A total of 61 patients had polysomnographic and adherence data analysed, 30 were given SleepMapper and 31 received our standard of care. The two groups were well matched at baseline to include no significant differences in age, apnea–hypopnea index, percentage receiving split‐night polysomnographs and starting pressures. Patients in the control group received significantly more non‐benzodiazepine sedative hypnotics the night of their polysomnography and during positive airway pressure initiation. At 11 weeks, patients in the SleepMapper group had a greater percentage of nights with any use (78.0 ± 22.0 versus 55.5 ± 24.0%; P < 0.001) and >4 h positive airway pressure use (78.0 ± 22.0 versus 55.5 ± 24.0%; P = 0.02). There was a trend toward more patients in the SleepMapper group achieving >4 h of use for at least 70% of nights [9/30 (30%) versus 3/31 (9.7%); P = 0.06]. In multivariate linear regression, the SleepMapper remained significantly associated with percentage of nights >4 h positive airway pressure use ( β coefficient = 0.18; P = 0.02). Added to our usual, comprehensive programme to maximize positive airway pressure adherence in new users, the SleepMapper was independently associated with an 18% increase in nights >4 h of use.